2023
DOI: 10.3389/fpls.2023.1145510
|View full text |Cite
|
Sign up to set email alerts
|

Iron sensing in plants

Abstract: The ease of accepting or donating electrons is the raison d’être for the pivotal role iron (Fe) plays in a multitude of vital processes. In the presence of oxygen, however, this very property promotes the formation of immobile Fe(III) oxyhydroxides in the soil, which limits the concentration of Fe that is available for uptake by plant roots to levels well below the plant’s demand. To adequately respond to a shortage (or, in the absence of oxygen, a possible surplus) in Fe supply, plants have to perceive and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The factors mediating the transcriptional responses are not known in Chlamydomonas or other algae. We note that orthologs of MYB10 , PHR1 , BTSL1/2 , and bHLH34 involved in expression of the nutritional Fe regulon in land plants (Palmer et al 2013; Briat et al 2015; Vélez-Bermúdez and Schmidt 2023) are found in green algae as well (Urzica et al 2012; Roth et al 2017; Davidi et al 2023) (Supplemental Dataset S8).…”
Section: Discussionmentioning
confidence: 99%
“…The factors mediating the transcriptional responses are not known in Chlamydomonas or other algae. We note that orthologs of MYB10 , PHR1 , BTSL1/2 , and bHLH34 involved in expression of the nutritional Fe regulon in land plants (Palmer et al 2013; Briat et al 2015; Vélez-Bermúdez and Schmidt 2023) are found in green algae as well (Urzica et al 2012; Roth et al 2017; Davidi et al 2023) (Supplemental Dataset S8).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are hints that Fe-S clusters may be involved in iron sensing pathways, but no definitive evidence has been found to date [196]. As mentioned above, IRP1 has dual function as an RNA binding, iron response protein, and alternatively, as a cytosolic aconitase.…”
Section: Plant Iron Sensing Iron-sulfur Clustersmentioning
confidence: 99%
“…Further, iron is distributed to the sink tissues and utilized in the formation of enzyme cofactors, etc., or stored in vacuoles or complexed with ferritins. The mechanisms and regulations of iron homeostasis in plants have been extensively reviewed in recent years [ 94 , 95 , 96 , 97 , 98 , 99 ]. Here, we focus the discussion on recent advances in the understanding of plant iron homeostasis in the context of microbial infections and plant host responses.…”
Section: Interplay Between Iron Homeostasis and Plant Immune Responsementioning
confidence: 99%